Association between cervical length and massive intraoperative bleeding in patients with suspected placenta accreta spectrum combined with placenta previa: A retrospective cohort study - Huang, Fusen; Wang, Jingjie; Xu, Yi; Xiong, Qiuju; Wang, Wenjian; Zhuo, Jia; Xia, Qiuling; Yang, Xiaojuan (Frontiers in Surgery, 2022)
Purpose: PAS can easily lead to life-threatening hemorrhage. The predictive value of cervical length (CL) in patients with PAS was controversial. Thus, this study investigated the relationship between CL and the probability of major bleeding in patients with PAS combined with placenta praevia. Methods: This retrospective cohort study was conducted in a comprehensive tertiary hospital in Chongqing, China, between January 2018 to December 2020. The target independent variable and the dependent variable were CL and intraoperative massive bleeding respectively. Covariates included demographic, clinical characteristics, and ultrasound characteristics. Logistic regression was applied to explore the association between the level of CL and massive bleeding. Results: A total of 317 participants were included, and the prevalence of massive bleeding was 41.9% (133/317). The threshold of CL associated with massive bleeding (≥1000 mL) was 33 mm, based on a receiver operating characteristic (ROC) curve. In the fully-adjusted model for each additional one unit of CL, the risk of massive bleeding decreased by 7% (95% CI, 0.88-0.98). And the risk of major bleeding was reduced by 44% in patients with a CL greater than 33 mm (95% CI, 0.33-0.97), compared with patients with a CL less than 33 mm. Conclusions: CL is negatively associated with intraoperative massive bleeding in patients with PAS combined with placenta praevia. When the CL is greater than 33 mm, the risk of bleeding decreased by 44% (95% CI, 0.33-0.97). Thus, CL, as a standalone parameter, can aid in identifying women with massive intraoperative bleeding in suspected PAS.